Association between severe acute malnutrition during childhood and blood pressure during adulthood in the eastern Democratic Republic of the Congo: the Lwiro cohort study - Pacifique Mwene-Batu; Daniel Lemogoum; Laurène de le Hoye; Ghislain Bisimwa; Michel P. Hermans; Jimmy Minani; Gaylord Amani; Guy-Quesney Mateso; Justin Cirhuza Cikomola; Michelle Dramaix; Philippe Donnen (BMC, 2021)
Abstract Introduction Little is known about the long-term outcomes of Severe Acute Malnutrition (SAM) during childhood. As such, this study aims to explore the association between childhood SAM and blood pressure (BP) in adulthood in a context without nutrition transition. Methodology We identified 524 adults (Median age: 22 years) who were treated for SAM during childhood in Eastern DRC between 1988 and 2007. They were compared with 407 age-and-sex matched subjects with no history of SAM in the community. The variables examined for this study were the systolic (SBP), diastolic (DBP), mean (MBP) blood pressure (BP) and pulse pressure (PP), as well as high blood pressure (HBP) defined as BP ≥ 140/90 mmHg and/or use of BP-lowering drug(s) in adulthood. For comparison, linear and logistic regression models were used for analysing continuous and dichotomous variables, respectively. Results Of the 524 exposed located, 145 were selected according to age. A total of 97 unexposed were recruited. Compared to unexposed, exposed had slightly higher SBP and PP after adjusting for occupation, body mass index (BMI) and food consumption [SBP = 1.4 mmHg (− 2.2, 4.8) and PP = 2.6 mmHg (− 0.3, 6.0)]. However, their DBP was lower than that of the unexposed [− 1.6 mmHg (− 4.6, 1.5)]. MBP and creatinine levels were similar between the two groups. The prevalence of HBP adjusted for age was higher among exposed than unexposed (9.7% vs 5.3%). In addition, the odds of having HBP was higher among exposed than unexposed, however the observed difference was not statistically significant [Odds Ratio (OR) 1.9 (0.7, 5.6)]. Finally, using multiple regression analysis, although the effect was not significant, SAM was a major contributor to HBP [adjusted OR 3.1 (0.9,10.9), p = 0.064], while only male gender and higher BMI (overweight/obesity) emerged as independent predictors of HBP among this young study population. Conclusions This study suggests that an episode of SAM in childhood has a weak impact on BP variability in young Congolese adults (from DRC) living in an environment without nutrition transition. However, people who experienced a period of SAM tended to have a higher prevalence of HBP and a much higher risk of developing HBP than unexposed. Additional multicentre studies involving a larger cohort would provide greater understanding of the impact of SAM on the overall risk of BP disorders during adulthood.